The ritual artistic presence of the Marionette actor: in the performance of the play (Tokoos alhatab) - Wissam khider musa; Nashat Mubarak Sliwa (Basrah Arts Journal, 2024)
The research dealt with the ritual artistic presence of the marionette actor, relying on a series of formation principles in scenic construction, in addition to its reliance on the transformation of the actor’s physical and psychological capabilities as a product of the philosophical awareness of the era. The actor acquires them and thus resembles the absent other and gives him a spirit that makes him an active presence, then transforms him into an object. (Marionette) with a mass that is organized and harmonious in its composition and formation. Therefore, the research was founded on four chapters. The first (methodological framework) contained the research problem, which was defined by the following question (What is the ritualistic artistic presence of the marionette actor in the firewood ritual show?), and the goal of the research is (to identify the ritualistic artistic presence of the marionette actor in light of technical harmony). The second (theoretical framework) included two sections, the first dealing with (presence in philosophical opinions), and the second (the ritual artistic presence of the marionette actor in theatrical experiences). The third chapter included the research procedures, and the fourth chapter included the results and conclusions that confirmed the effectiveness of the actor’s ritual presence through technology. A performance revealed by the show’s actor, in which the process of transformation between self and other went through several stages that formed a tangible and influential ritual reality.